1985
DOI: 10.1073/pnas.82.17.5865
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Drosophila small hsp-tk hybrid genes is induced by heat shock and by ecdysterone in transfected Drosophila cells.

Abstract: Hybrid genes containing the 5' region of Drosophila heat shock protein (hsp) genes, ligated to the herpesvirus thymidine kinase (tk) gene, were transfected into Drosophila line S3 cells. Constructions containing sequences upstream from hsp7O, or from any of the small hsp genes, showed heat-inducible tk expression. Ecdysterone-inducible tk expression was seen only in transfections with small hsp-tk hybrid genes. Plasmids containing a synthetic "heat shock consensus sequence" or a deletion of the hsp23 upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1

Year Published

1986
1986
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…First, ecdysterone induction is based on an increased level of new transcription. This is true for expression of both endogenous s-hsp genes (55) and a reporter gene put under the regulatory control of an s-hsp gene promoter (32,33). There is no evidence to suggest that ecdysterone alters the stability of endogenous s-hsp transcripts (55), or mRNAs transcribed from reporter genes, such as the chloramphenicol acetyl * Corresponding author.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…First, ecdysterone induction is based on an increased level of new transcription. This is true for expression of both endogenous s-hsp genes (55) and a reporter gene put under the regulatory control of an s-hsp gene promoter (32,33). There is no evidence to suggest that ecdysterone alters the stability of endogenous s-hsp transcripts (55), or mRNAs transcribed from reporter genes, such as the chloramphenicol acetyl * Corresponding author.…”
mentioning
confidence: 98%
“…transferase gene (CAT) or thymidine kinase gene (tk) (32,33). In addition, the response is quite specific.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All four of these developmentally regulated "small heat shock genes", along with a fifth developmentally regulated non-heat shock gene (R), are located within a 13-kilobase region on the left arm of chromosome 3 at 67B1 (10,51). Workers in other laboratories have recently published transcriptional regulation studies of these developmentally regulated heat shock genes in both heterologous monkey cells (1) and D. melanogaster cells (34).…”
mentioning
confidence: 99%
“…These studies have generally substantiated the importance of the heat shock consensus sequence (24), which binds the heat shock transcription factor both in vivo (35) and in vitro (22). The heat-induced regulation of the Drosophila small heat shock genes (hsp22, -23, and -27) has been studied in Xenopus oocytes (20), monkey cells (2,26), Drosophila cells (17,21), and germ line-transformed flies (5,(12)(13)(14)23 (3). It has been shown that a positioned array of nucleosomes occupies the coding but not the intergenic regions of these genes when in a transcriptionally inactive state.…”
mentioning
confidence: 99%